Multiple human papilloma virus infections predominant in squamous cell cervical carcinoma in Bandung - Edhyana Sahiratmadja; Maringan D.L Tobing; Birgitta M Dewayani; Bethy S Hernowo; Herman Susanto (Universa Medicina, 2014)
BACKGROUND Persistent infection of high risk genotypes of human papilloma virus (hrHPV) has been established as the etiological cause for cervical cancer, and the most prevalent genotypes that infect the cervical tissue are HPV-16 and HPV-18. However, HPV genotype profile has been shown to differ according to geographical distribution across the globe. The present study aimed to determine the HPV genotype distribution in cervical cancer patients from Bandung, Indonesia. METHODS During the period of July – November 2010 viral DNA was extracted from randomly chosen cervical cancer biopsies and subjected to genotype determination using the diagnostic linear array genotyping test (Roche). The distribution of HPV genotypes was explored and the prevalence of HPV genotypes was mapped. RESULTS Of 96 cervical cancer tissue samples, 76 (79.2%) were histopathologically classified as squamous cell cervical carcinoma. Due to the high cost of HPV genotyping tests, only twenty-five samples were randomly genotyped. Almost 90% of the cervical cancer patients were multiply infected with HPV-16 in combination with HPV-18, HPV-45, or HPV-52. The HPV-16 genotype had the highest prevalence, all samples being infected with HPV-16. CONCLUSION The cervical cancer cases were predominantly infected by multiple hrHPVs with HPV-16 as the major genotype among other hrHPVs, supporting the carcinogenic role of this hrHPV. Therefore, screening for hrHPVs in the general population is urgently needed as a means of early detection of cervical cancer.